Gender Studies and Character Education Values in the Novel "A Cup of Tea": A Critical Discourse Analysis - Marjuni, Marjuni; Ulwani, Adly Rosyad Fudhulul (Jurnal Pendidikan Islam, 2021)
This study aims to clarify that the novel "A Cup of Tea" by Gita Savitri Devi (GSD) can utilize a multidisciplinary approach to literary analysis using critical discourse analysis (CDA). This study poses three research questions: 1). Did the authors (GSD) link cyberbullying and the gender gap? 2). In the perspective of efforts to raise awareness about gender equality, how does GSD see the dangers of cyberbullying? 3). How can GSD's direct knowledge of the dangers of cyberbullying improve the struggle for gender equality? The CDA Qualitative Method was used to study "A Cup of Tea." Dijk's model uses a concept map to investigate literary works' structural and interactional paradigms. This study concludes that the writer's active and passive sentences have been examined. The structural paradigm includes the superstructure, macrostructure, and microstructure. This is complemented by some aesthetics that set the backdrop for the whole story. GSD's work is filled with anti-gender rhetoric and cyberbullying. Gita Savitri Devi is an outspoken advocate for women's rights. Women's emotional control must be exaggerated to show their work as skilled artists. GSD seems to be captivated by the future of Indonesia's young generation. The results of this study are very important to teach Indonesian youth about the dangers of cyberbullying and its relation to the issue of gender inequality. According to research, anti-cyberbullying strategies emphasize national character in online social interactions. The novel is useful as a media campaign against cyberbullying and the struggle for gender equality. Opportunities for further research on other types of literary works are urgently needed.